Laboratory monitoring during treatment of onychomycosis in pediatric patients: A survey of provider perspectives and practices. Issue 4 (4th June 2021) - Brockman, Ross; Funk, Tracy
Abstract: Background/objectives: Literature regarding the cost and necessity of laboratory monitoring during oral antifungal treatment in adults has recently been published. However, consensus guidelines for the treatment and monitoring of pediatric patients with systemic antifungals for onychomycosis are lacking. We sought to evaluate both the practice trends and perspectives of pediatric dermatology providers who treat pediatric onychomycosis. Methods: An electronic survey was administered to providers belonging to the Society for Pediatric Dermatology (SPD) and/or Pediatric Dermatology Research Alliance (PeDRA) regarding their clinical practice and reasoning for laboratory monitoring during the treatment of pediatric onychomycosis. Results: One hundred and twenty‐one providers completed the survey (12.5%). 77% identified themselves as pediatric dermatologists. A majority practice in the academic setting (51%), and 54% were primarily only pediatric providers. All respondents prescribe oral terbinafine for onychomycosis. 88% of respondents always or almost always confirm the diagnosis of onychomycosis prior to prescribing oral terbinafine for onychomycosis. 39% always or almost always routinely order baseline laboratory tests while 40% never or almost never do. 41% never or almost never order monitoring laboratory tests during treatment while 32% always or almost always do. 91.5% have never discovered a significant reaction to terbinafine with routine monitoring. Conclusion: Pediatric dermatology providers are very likely to confirm the diagnosis of onychomycosis prior to systemic treatment. Significant variability was found in pretreatment and treatment laboratory monitoring, reasons for laboratory monitoring or deferral of testing, and timing of testing among providers. Knowledge of current practice trends as well as provider perspectives may be useful in the future development of consensus guidelines.